2013
DOI: 10.1186/1471-2458-13-780
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alcohol use before and during pregnancy and predictors of drinking during pregnancy: a cross sectional study in Sweden

Abstract: BackgroundThere is a paucity of research on predictors for drinking during pregnancy among women in Sweden and reported prevalence rates differ considerably between studies conducted at different antenatal care centres. Since this knowledge is relevant for preventive work the aim of this study was to investigate these issues using a multicenter approach.MethodsThe study was conducted at 30 antenatal care centers across Sweden from November 2009 to December 2010. All women in pregnancy week 18 or more with a sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
61
5
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 37 publications
13
61
5
10
Order By: Relevance
“…Women who drank more than two alcoholic drinks per week or more than five alcoholic drinks per occasion (binge drinking) before they became pregnant, found it significantly more difficult to abstain entirely from drinking alcohol during pregnancy [55,60,65]. The same applied to pregnant women who had additionally smoked before or during pregnancy [55,[63][64][65][66]. Two of the studies found a correlation between continued maternal alcohol consumption and unplanned pregnancy [55,60]; it was not clear, however, whether nullipara or multipara found it more difficult to abstain from drinking alcohol [36].…”
Section: Continued Next Pagementioning
confidence: 98%
See 1 more Smart Citation
“…Women who drank more than two alcoholic drinks per week or more than five alcoholic drinks per occasion (binge drinking) before they became pregnant, found it significantly more difficult to abstain entirely from drinking alcohol during pregnancy [55,60,65]. The same applied to pregnant women who had additionally smoked before or during pregnancy [55,[63][64][65][66]. Two of the studies found a correlation between continued maternal alcohol consumption and unplanned pregnancy [55,60]; it was not clear, however, whether nullipara or multipara found it more difficult to abstain from drinking alcohol [36].…”
Section: Continued Next Pagementioning
confidence: 98%
“…Multipara were found to be a group at particular risk of continuing to smoke during pregnancy compared to women who were pregnant with their first child or women who had previously given birth to only one child [32, 35, 56-57, 65, 67]. In contrast to maternal nicotine consumption the consumption of low to moderate amounts of alcohol during pregnancy is a risk factor which was more likely to affect women with a higher socio-economic status and women who were older (aged > 30 years) [34,61,63,66]. Skagerstróm et al [36], who summarized the findings of 14 studies published between 2002 and 2009, did not come to a definitive conclusion with respect to the impact of the pregnant womanʼs social status on her prenatal consumption of alcohol.…”
Section: Continued Next Pagementioning
confidence: 99%
“…131 A Swedish study found that older age, living in a major city with low social support and using tobacco during pregnancy, as well as pre-pregnancy drinking, were predictors of women's drinking in pregnancy. 132 It has been suggested that increased awareness of the dangers of drinking in pregnancy has resulted in changes in women's behaviour, 133 but this may simply be a case of women reporting less alcohol consumption.…”
Section: Prevalence Of Alcohol Consumption In Pregnancymentioning
confidence: 99%
“…This relates to the concept of social capital, which suggests that social connectedness in itself has a positive effect on health status [34]. We also know that families and friends influence women's decision to drink or to abstain from alcohol [35] and that higher social support before pregnancy is associated with decreased risk of drinking during pregnancy [36]. Systematic reviews of interventions delivered during prenatal care suggest that there are examples of successful interventions, but their effectiveness varies overall [19] [33] [37].…”
Section: Introductionmentioning
confidence: 99%